The evolution of hydrochemical and isotopic signatures from precipitation, surface water to groundwater in a typical karst watershed, Central Texas, USA. Issue 5 (3rd September 2021) - Tian, Lijun; Gao, Yongli; Yang, Guang; Schwartz, Benjamin; Cai, Binggui; Lei, Guoliang; Shi, Guitao; Ray, Christopher; Sok, Soeuth; Martinez, Erica; Li, Yunxia; Wu, Haibin
ABSTRACT: The Upper Cibolo Creek (UCC) karst watershed in Central Texas, USA, represents a portion of the drainage area that supplies water to the recharge zone for the Edwards Aquifer. However, the surface water–groundwater interactions along the UCC are not well quantified, and the hydraulic interactions are important for water budget and water quality of the aquifer. In this study, we investigated the evolution of hydrochemical and isotopic signatures ( δ 18 O, δ 2 H and d -excess) from precipitation, surface water to groundwater in the UCC watershed from 2017 to 2019, and investigated surface water–groundwater interactions using samples from 14 creeks/spring sites. Factor analysis for the observed parameters demonstrates that changes in water hydrochemistry are primarily controlled by human activity, precipitation input, and water–rock interaction. Hierarchical clustering analysis of temporal isotope variations confirms that significant surface water–groundwater interactions occur in the UCC watershed. We identified relationships between nitrate concentrations at creek/spring sites and land-use conditions, and nitrate input sources were determined utilizing the dual-isotope analyses ( δ 15 N and δ 18 O) of nitrate. This study provides capacity for a more precise assessment of water resources and water quality in Central Texas.